Model Pengaruh Modal Sosial Mahasiswa Terhadap Minat Kunjung Ulang (Revisit Intention) yang Dimediasi Oleh Kepuasan Mahasiswa atas Layanan Perpustakaan - Febrianti, Beta Ria; Saptawan, Ardiyan; Alamsyah, Alamsyah (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
This study aims to determine the model of the influence of student social capital on revisit intention mediated by student satisfaction with the services of the Sriwijaya University Library. The population in this study were Sriwijaya University students who made offline visits (face to face) who visited the Sriwijaya University Library in 2021 who returned as many as 16,395 people. Determining the sample using the Slovin formula with incidental sampling technique. The data collection technique used was by distributing questionnaires to 99 students who visited the Sriwijaya University Library. This study uses primary data obtained from the distribution of questionnaires. The analysis technique in this study uses path analysis and Sobel test to test the mediating variables. The results of this study indicate that the better the student's social capital, the higher the level of student satisfaction. student goals have a dominant or strong influence on the interest in repeat visits. The direct influence of student social capital on interest in visiting has a moderate effect because it depends on other variables, including student satisfaction with the services of the Sriwijaya University Library. Social capital has an indirect effect on interest in revisiting (revisit intention), the increase in interest in revisiting when viewed from student social capital will be real if viewed from student satisfaction with the services of the Sriwijaya University Library.